ATRIAL FIBRILLATION AND STROKE RISK: PREVENTION STRATEGIES AND PUBLIC HEALTH IMPLICATIONS - Ziemba-Furgała, Natalia Matylda; Szwed, Agnieszka; Borzęcka , Katarzyna Anna; Polewczak-Karp, Ewa Maria; Warzocha-Żurek, Daria Aleksandra; Andryszko , Krystian; Sołtys , Aleksandra; Dymon , Marcelina; Krysa , Paulina; Wawrzonek , Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Atrial fibrillation is the most common sustained cardiac arrhythmia and a major risk factor for stroke. The aim of this review is to present the relationship between AF and stroke risk through an analysis of current epidemiological data, pathophysiological mechanisms, risk factors, and prevention strategies. This review is based on an analysis of recent literature and clinical guidelines. Patients with atrial fibrillation have a significantly increased risk of stroke, which is often associated with greater severity and poorer outcomes. Risk stratification tools such as CHA₂DS₂-VASc and HAS-BLED play a key role in guiding individualized therapy. Anticoagulation remains the cornerstone of stroke prevention, supported by management of risk factors and lifestyle modification. Early detection, particularly in asymptomatic patients, is also crucial. Despite the availability of effective preventive strategies, their implementation in clinical practice remains suboptimal. Effective stroke prevention requires an integrated approach combining risk assessment, appropriate treatment, and early diagnosis.